2008
DOI: 10.1074/jbc.m706238200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Interacting Elements in K-Ras/Calmodulin Binding and Its Role in K-Ras Localization

Abstract: We previously showed that K-Ras is a calmodulin-binding protein. Involvement of this interaction in anterograde and retrograde transport of K-Ras was then suggested. To test this we have analyzed here the domains of K-Ras essential for the interaction with calmodulin. At least three different regions in the K-Ras molecule were important; they are the hypervariable region, the ␣-helix between amino acids 151 and 166, and the Switch II. Within the hypervariable region, both the hydrophobic farnesyl group and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 51 publications
7
92
2
Order By: Relevance
“…In fact, certain groups have reported that phosphomimetic K-Ras is internalized to intracellular membranes, such as those in mitochondria, the Golgi complex, the endoplasmic reticulum or in endosomes (Bivona et al, 2006;Fivaz and Meyer, 2005). However, in agreement with previous observations (Lopez-Alcalá et al, 2008;Plowman et al, 2008), we show here that, after simultaneous transfection of YFP-K-RasG12V-S181A and mCherry-K-RasG12V-S181D into HEK293 cells, both phospho-mutants are mainly located at the plasma membrane ( Fig. 2A).…”
Section: Resultssupporting
confidence: 79%
“…In fact, certain groups have reported that phosphomimetic K-Ras is internalized to intracellular membranes, such as those in mitochondria, the Golgi complex, the endoplasmic reticulum or in endosomes (Bivona et al, 2006;Fivaz and Meyer, 2005). However, in agreement with previous observations (Lopez-Alcalá et al, 2008;Plowman et al, 2008), we show here that, after simultaneous transfection of YFP-K-RasG12V-S181A and mCherry-K-RasG12V-S181D into HEK293 cells, both phospho-mutants are mainly located at the plasma membrane ( Fig. 2A).…”
Section: Resultssupporting
confidence: 79%
“…This regulatory mechanism has already been shown for other CaM-binding proteins, such as neurogranin, neuromodulin, myristylated alanine-rich C-kinase substrate (Chakravarthy et al, 1999) and p21 (Rodriguez-Vilarrupla et al, 2005;Agell et al, 2006). In analogy to other CaM-binding proteins, phosphorylation within the CaM-binding region of K-Ras inhibits its binding to CaM (Lopez-Alcala et al, 2008). Thus, also for K-Ras, there is an antagonism between CaM and PKC: CaM inhibits phosphorylation by PKC and phosphorylation inhibits binding of CaM.…”
Section: Discussionmentioning
confidence: 68%
“…We have shown that CaM inhibition specifically enhances K-Ras activation provided protein kinase C (PKC) is active. It is interesting that we have also demonstrated that K-Ras is a CaM-binding protein, although it is only able to bind CaM if it is GTP-bound and not phosphorylated at Ser181, suggesting an interplay between CaM binding to K-Ras, K-Ras phosphorylation and K-Ras activity (Villalonga et al, 2001Lopez-Alcala et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations